Mutu Organoleptik Cookies Substitusi Tepung Beras Hitam dan Tepung Kacang Merah sebagai Alternatif Makanan Selingan Penderita Diabetes Mellitus - Fira Yunia Ersanti; Miftahul Munir (Yayasan Literasi Sains Indonesia, 2024)
Diabetes mellitus is a chronic condition characterized by high blood sugar levels. To maintain stable blood sugar, it is recommended to consume foods with a low glycemic index and rich in fiber, such as black rice and red beans. Therefore, making cookies with black rice flour and red bean flour substitution can be an alternative healthy snack for people with diabetes mellitus. This study aims to determine the effect of black rice flour and red bean flour substitution on the organoleptic quality of cookies. This study used True Experimental Design with the Completely Randomized Design (CRD) method, consisting of 4 treatments and 6 replications. The ratio of wheat flour, black rice flour, and red bean flour in each formula was P0 (100:0:0), P1 (0:25:75), P2 (0:50:50), and P3 (0:75:25). Organoleptic tests were conducted by 30 untrained panelists in Tobo Village, Merakurak District, Tuban Regency. Data were analyzed using the Kruskal-Wallis test, followed by the Mann-Whitney test. The results of this study indicate that there are significant differences (p<0.05) in the categories of color, taste, aroma, and texture of cookies. The best treatment based on organoleptic tests is in the P2 cookie formulation. This study concludes that the substitution of black rice flour and red bean flour can affect the organoleptic quality of cookies.